Globalization/Human Safety: A Biopolitical Approach - Kravets, Anastasia (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
Biopolitics focuses on the impact of globalization on the well-being of the individual and society as a whole. Accordingly, issues of human security and the threats posed by the process of globalization, as well as the transition from a disciplinary regime to a regime of governance at the global level, which, based on democratic values and liberal norms, are raised. That is why the problem of social justice and equality is solved. The issue of human safety within global governance should be emphasized. It is about a sense of security as a basic human need. Moreover, it is about the global security necessary for the survival and reproduction of humanity as a whole. As well as the study of potential socio-political consequences of the development of biotechnology and genetic engineering in the global dimension. This huge set of issues must be concretized, systematized, and logically structured through the analysis of the impact of globalization on the state of the individual, its relationship with the concept of bios; introduction at the international level of the doctrines of social justice, protection of human and civil rights at the global level; study of potential socio-political consequences of the development of biotechnology in the global dimension; introduction of new biopolitical models of power, governance and international relations; analysis of the theory of global evolution.

Biopolityka skupia się na wpływie globalizacji na dobrobyt jednostki i społeczeństwa jako całości. W związku z tym podniesiono zagadnienia związane z kategorią bezpieczeństwa człowieka, zagrożeniami stwarzanymi przez globalizację oraz tranzycją od reżimu dyscypliny do reżimu zarządzania w skali globalnej opartego na demokratycznych wartościach i liberalnych normach. Z tego powodu zajęto się także kwestią sprawiedliwości społecznej i równości. Podkreślenia wymaga jednak kategoria bezpieczeństwa człowieka w systemie globalnego zarządzania. Dotyczy ona bowiem poczucia bezpieczeństwa jako podstawowej potrzeby ludzi. Ponadto dotyczy także konieczności zagwarantowania bezpieczeństwa globalnego dla przetrwania i reprodukcji gatunku ludzkiego. W studium zawarto możliwe społeczno-ekonomiczne konsekwencje rozwoju biotechnologii i inżynierii genetycznej w skali światowej. Zarysowany, bardzo szeroki zbiór zagadnień, należy skonkretyzować, usystematyzować i logicznie ustrukturyzować na podstawie analizy wpływu globalizacji na kondycję jednostki, jej relacji do koncepcji bios; wprowadzenia doktryny sprawiedliwości społecznej na poziomie międzynarodowym, ochrony praw człowieka i obywatelskich w wymiarze globalnym; wprowadzenia nowych, biopolitycznych modeli władzy, rządzenia i relacji międzynarodowych; oraz teorii globalnej ewolucji.
Globalizacja/bezpieczeństwo człowieka: perspektywa biopolityczna
Keywords: bios; biopolitics; biopower; globalization; human safety; biotechnologies; biopolityka; biowładza; globalizacja; bezpieczeństwo człowieka; biotechnologia